2014
DOI: 10.1155/2014/787595
|View full text |Cite
|
Sign up to set email alerts
|

Laser Induced Modification of the Optical Properties of Nano-ZnO Doped PVC Films

Abstract: The effect of continuous CO2laser radiation on the optical properties of pure polyvinyl chloride and doped of ZnO nanoparticles with two different concentrations (10, 15%) has been investigated. All samples were prepared using casting method at room temperature. Optical properties (absorption, transmission, absorption coefficient, extinction coefficient, refractive index, and optical conductivity) of all films after CO2laser irradiated have been studied as a function of the wavelength in the range (200–800) nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus, it is important to determine optical constants of the films. The refractive index of the films was determined from the following relation [18]:…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is important to determine optical constants of the films. The refractive index of the films was determined from the following relation [18]:…”
Section: Resultsmentioning
confidence: 99%
“…The absorption coefficient of (PMMA-ZrO 2 -Ag) nanocomposites is less than 10 4 cm 1 ; this clarifies that the electron transition is indirect [101].…”
Section: Resultsmentioning
confidence: 70%
“…1a shows the absorption curves as a function of wavelength in prepared chitosan solution samples. Through our observation of the Figure , it was found that the behavior of the curves is the same for all models before and after irradiation, where a sudden increase was noted in the absorption values in wavelength range (250-400) nm and this might be due to a decrease in the absorption of the incident beam [11]. Then the curve begins to nearly stabilize after wavelengths higher than (400) nm.…”
Section: Absorbancementioning
confidence: 69%